The Influence Of Corporate Culture And Internal Control Systems On The Prevention Of Merchandise Fraud - Rahmawati, Laela; Pradata, Bramastyasa Gilang (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Fraud is a problem that can hinder the achievement of company goals and is usually carried out by individuals who have experience in their field which occurs due to opportunities and conflicts of interest. Therefore, companies need tools that can help in terms of corporate culture or the values that underlie the company's identity, such as regulatory attitudes that employees in the company must have and internal controls such as internal audits. The purpose of this research is to test and find out how much influence company culture and internal control have on preventing goods fraud. Data collection was carried out through distributing questionnaires whose validity and reliability had been tested. For the results of this research, the influence of company culture (X1 ) on preventing goods fraud (Y) has a significant effect. This shows that the better the corporate culture in a company, the better the prevention of goods fraud. For the results, the influence of internal control (X 2 ) on the prevention of goods fraud (Y) has a significant effect. This shows that the better the internal control carried out in the company, the better the prevention of goods fraud . Keywords: Company Culture, Control System, Merchandise Fraud